THE RESULTS OF TREATMENT CHEMICAL BURNS AND OF POST-BURN CICATRICAL ESOPHAGEAL STRICTURES (LITERATURE REVIEW) - M. L. Voskresenskaya; A. N. Piekhanov (Acta Biomedica Scientifica, 2015)
According to different authors, cicatricial changes due to chemical bums of a gullet fluctuate in the big range from 3 to 74 %. Chemical esophagus burn of III degree leads to post-bum scar stricture of the esophagus in 15-70 % of cases. Bougienage, stenting, balloon dilatation are the most effective and safe in 70-96 % of patients. Bougienage is a leading method today. Developing promising direction - stenting with the use of new technologies. Despite the success of minimally invasive surgery in the treatment of stricture, 10-50 % of patients require surgical treatment. For the moment, despite high traumatic and high percent ofstricture relapse (15-40 %), and also exitus letalis coming up to 10%, bougienage is the basic and most effective method of treatment.